1987
DOI: 10.1016/s0735-1097(87)80475-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of repeated episodes of drug-induced ventricular dyskinesia on subsequent regional function in the dog: Comparison with myocardial stunning produced by repeated coronary occlusions

Abstract: Stunned myocardium can be produced by repeated short episodes of ischemia. Histochemical and ultrastructural abnormalities such as sarcomere lengthening and myofiber thinning have been noted in myocardium soon after the onset of ischemia and have been attributed to the mechanical stretching that occurs during ventricular systole. To test whether mechanical forces alone could produce the residual dysfunction seen in stunned myocardium, regional dyskinesia was produced in open chest dogs by six repeated intracor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Although KCI can produce primary vasoconstriction, ischemia is unlikely. In contrast to ischemia, discontinuation of the regional KCI infusion results in complete restoration of function (11,14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although KCI can produce primary vasoconstriction, ischemia is unlikely. In contrast to ischemia, discontinuation of the regional KCI infusion results in complete restoration of function (11,14).…”
Section: Discussionmentioning
confidence: 99%
“…In three dogs, potassium chloride (KCI) at a concentration of 1.0 mEq/ml was infused into the LAD perfusion line at a rate of 0.34 or 0.68 ml/min in order to abolish regional myocardial contraction (11,14). After 10 min of regional cardioplegia the segment length was recorded.…”
Section: Coronary Occlusion During Regional Eardioplegia Group (Groupmentioning
confidence: 99%
“…The time course of changes in the ∆ST and %SS appeared simultaneously with equal severity (Fig 4). Experimental models of drug-induced ventricular dyskinesia have been reported in other studies, 11,12 in which lidocaine and potassium chloride were used. In our study, 4 different agents that modify different ion channels showed similar results on ventricular dyskinesia and ST-segment elevation.…”
Section: Selection Of Negative Inotropic Agentsmentioning
confidence: 99%
“…These mechanical changes could have altered the transmembrane potential and action potential duration due to mechanoelectrical feedback effects. 12 Mechanoelectrical feedback is defined as electrophysiological changes caused by mechanical effects or a hemodynamic loading condition, and is believed to be a cause of arrhythmogenesis in the presence of heart failure. 13 Lab demonstrated that stretching of the ventricular myocardium of frogs caused shortening of the action potential and depolarization of the resting potential.…”
Section: Regional Dyskinesia and St-segment Elevationmentioning
confidence: 99%
“…We performed experiments in three groups of anaesthetised closed-chest pigs. In the first group we created myocardial stunning using repetitive ischaemia–reperfusion 6. We measured regional function in vivo using tagged magnetic resonance imaging (MRI) and measured myocardial water content (MWC) post mortem.…”
mentioning
confidence: 99%